MEASURES MOTIVATING TEACHERS: A STUDY IN VILNIUS CITY MUNICIPALITY - Zibeniene, Gintaute; Zemaitaityte, Irena; Gudelis, Dangis; Stasiukynas, Andrius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Recently, there has been significant conversation surrounding the issue of a lack of teachers and the difficulties in retaining them. One question being asked is how to make teaching positions more appealing in order to attract educators. This is a concern in multiple countries, specifically in Lithuania, where there is a lack of educators in schools, and a higher proportion of older teachers compared to the European average (per Eurostat data). Although Lithuanian municipalities pay a monthly bonus of €300-500 in the first year and provide housing benefits to attract teachers, these measures do not sufficiently motivate teachers.The aim of this paper is tohighlight the measures that motivate teachers to work as teachersin relation tothe recognition of teachers' competence, communication and cooperation. The authors of the article conducted a study to find out what motivates teachers to do pedagogical work (Stasiukynas, Zemaitaityte, Gudelis, Zibeniene, 2020). The paper presents results of the part of this large study, which involved 873 teachers. In April and May of 2020, a survey of teachers in the city of Vilnius was conducted using the online survey platform Qualtrics. The research adhered to principles of ethical scientific conduct. Participants were given the freedom to participate and withdraw at any time, were informed of the study's purpose, data usage, and their anonymity was protected. The researchers also committed to upholding ethical standards and safeguarding participants from any potential harm. The survey data analysis showed that teachers considered working collaboratively with their peers within the educational institution as a crucial factor in motivating them in their teaching roles.Leisure time with colleagues in joint outings outside the educational institution and the opportunity to meet colleagues from different countries to share good practices were also highly rated by respondents. Reducing the administrative burden on teachers and protecting and safeguarding teachers' rights were also highlighted as important motivational factors. In order to retain already working teachers and attract new ones, teachers expressed the expectation that confidence in teachers' opinions and professional competence would be increased.